Enantioselective Organocatalytic Thiol Addition to α,β-Unsaturated α-Amino Acid Derivatives - Breman, Arjen C.; Smits, Jan M. M.; de Gelder, Rene; van Maarseveen, Jan H.; Ingemann, Steen; Hiemstra, Henk (Synlett, 2012)
A new class of Michael acceptors based on α,β-unsaturated amino acids has been prepared and applied in asymmetric organocatalysis. With the use of thiourea derivatives of cinchona alkaloid-derived catalysts, efficient addition of thiols to the dehydroamino acids occurred with formation of β-thiol functionalized α-amino acids in high yields, moderate diastereoselectivities and ee values up to 95%.
Keywords: organocatalysis; cinchona alkaloids; amino acids; thiols; conjugate addition